2012
DOI: 10.3389/fendo.2012.00123
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of cholecystokinin receptors to membrane cholesterol content

Abstract: Cholesterol represents a structurally and functionally important component of the eukaryotic cell membrane, where it increases lipid order, affects permeability, and influences the lateral mobility and conformation of membrane proteins. Several G protein-coupled receptors have been shown to be affected by the cholesterol content of the membrane, with functional impact on their ligand binding and signal transduction characteristics. The effects of cholesterol can be mediated directly by specific molecular inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 106 publications
0
26
0
Order By: Relevance
“…This receptor has been shown to be uniquely sensitive to the membrane cholesterol composition (12,13), with the closely structurally related type 2 CCK receptor (CCK2R) not sensitive to membrane cholesterol (14). This effect has been demonstrated not only in model cell systems (15) but also in the natural cellular environment in animal models, such as the prairie dog fed a high cholesterol diet (16), and even in patients with cholesterol gallstones (17)(18)(19).…”
mentioning
confidence: 99%
“…This receptor has been shown to be uniquely sensitive to the membrane cholesterol composition (12,13), with the closely structurally related type 2 CCK receptor (CCK2R) not sensitive to membrane cholesterol (14). This effect has been demonstrated not only in model cell systems (15) but also in the natural cellular environment in animal models, such as the prairie dog fed a high cholesterol diet (16), and even in patients with cholesterol gallstones (17)(18)(19).…”
mentioning
confidence: 99%
“…Of note, the closely-related CCK2R is not affected (4). This defect in CCK1R function is not observed in patients with pigment gallstones (3, 25), who are known to have similar levels of gallbladder inflammation, yet normal levels of cholesterol in their bile (27). Our previous in vitro studies using site-directed mutagenesis of CCK1R and model cell systems have suggested that the negative impact of elevated cholesterol on CCK1R function was mediated by a direct interaction between the two molecules resulting in an abnormal receptor conformation (5, 21).…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is reported to exhibit dysfunction in the setting of high membrane cholesterol, such as has been reported in metabolic syndrome and cholesterol gallstone disease. Several in vitro and in vivo studies have demonstrated that the CCK1R is uniquely sensitive to an increase in cellular membrane cholesterol, which negatively affects effective coupling between Gq and this receptor, thereby resulting in reduced biological responses to CCK (see review (3)). Included among the defective biological responses is post-cibal satiety, contributing to increased weight gain and increasingly severe obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral allosterism through lipid interactions is now appreciated as a way to modulate GPCR function [49]. The CCK1R has been shown to be particularly sensitive to the cholesterol composition of the lipid bilayer [50, 51]. Membrane cholesterol elevated to levels reported in metabolic syndrome [52, 53], result in functional uncoupling of CCK binding from CCK-stimulated biological activity [50, 5456].…”
Section: Allosteric Modulation Of Endogenous Agonist Actionmentioning
confidence: 99%